Pengaruh Financial Distress, Intensitas Asset Tetap dan Sales Growth pada Tax Avoidance pada Perusahaan Consumer Non-Cyclicals Sub Sektor Food and Beverage Tahun 2019 - 2022 - Uliganda, Ruth Maria; Hermi, Hermi (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
Tax Avoidance is a commonly observed phenomenon. The government has made various efforts to suppress Tax Avoidance, but it still faces many challenges. This research aims to examine financial distress, fixed asset intensity, and sales growth in relation to Tax Avoidance. The research focuses on companies in the consumer non-cyclicals subsector of food and beverage listed on the Indonesia Stock Exchange during the period from 2019 to 2022. The research method employed is descriptive research with a quantitative approach. Purposive sampling is used as the sampling technique. Based on predefined criteria, a total of 50 companies from the consumer non-cyclicals subsector of food and beverage listed on the Indonesia Stock Exchange during the period 2019 to 2022 were selected. The data analysis techniques used in this research include descriptive analysis, classical assumption tests, coefficient of determination tests, and hypothesis testing. The research findings indicate that financial distress has a positive effect on Tax Avoidance. Additionally, fixed asset intensity also has a positive effect on Tax Avoidance. Meanwhile, sales growth shows a positive influence on Tax Avoidance